2021
DOI: 10.3390/cancers13246290
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Peptide-Receptor Radionuclide Therapy in Elderly Neuroendocrine Tumor Patients

Abstract: Peptide receptor radionuclide therapy (PRRT) is a well-established treatment in somatostatin receptor-expressing neuroendocrine tumours (NETs). The safety and efficacy of PRRT in >79 years old patients (EP) have not been systematically investigated. All patients with inoperable/metastatic/progressive G1/G2 NET, >79 years (EP), treated with PRRT at the University Hospital of Basel between 2006 and 2018, were enrolled in this retrospective matched cohort study. Each patient was manually matched with ≥1 you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…In this study, we analyzed the prediction of survival in patients treated with PRRT therapy in a cohort of 51patients with welldifferentiated NETs from different sites of primary origin. According to the literature, the median age at diagnosis of NETs typically falls within the range of 61-69 years (3,(15)(16)(17)(18)(19). Consistent with these findings, our study also revealed a similar pattern, with mean age of 59.83 ± 10.83.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, we analyzed the prediction of survival in patients treated with PRRT therapy in a cohort of 51patients with welldifferentiated NETs from different sites of primary origin. According to the literature, the median age at diagnosis of NETs typically falls within the range of 61-69 years (3,(15)(16)(17)(18)(19). Consistent with these findings, our study also revealed a similar pattern, with mean age of 59.83 ± 10.83.…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, it has been reported that patients over 40 years of age have an increased risk of death ( 15 17 ), although the clinical benefit of PRRT is satisfactory in both older and younger patients ( 16 ). In the literature, it has been shown that females tend to have better survival compared to males in the context of NETs ( 18 , 19 ). However, our study did not find a significant association between gender and survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…in the group of 116 patients that was separated in elderly cohort (n = 48; age 81.7 ± 1,5), and younger cohort (n = 68; age 67.6 ± 1,7), we also confirmed that older age of patients is not connected with higher number of adverse events in long-term observation. This conclusions confirms the fact that RLT can be administrated in all age groups [ 16 ].…”
Section: Discussionsupporting
confidence: 84%
“…PRRT was also reported to be safe in the elderly (Theiler et al described a comparable safety profile in young and elderly patients aged > 79) [ 17 ] and in patients with chronic kidney disease [ 18 ].…”
Section: Updates In Prrtmentioning
confidence: 99%